DISPUTE RESOLUTION BETWEEN PROPERTY DEVELOPERS AND PURCHASERS IN HOUSING CREDIT DEFAULT CASES INVOLVING BUYBACK GUARANTEE MECHANISMS - Soewono, Francisca (jfpublisher, 2025)
This research examines dispute resolution mechanisms between property developers and purchasers in cases of housing mortgage default that trigger buyback guarantee provisions. The primary challenge confronting purchasers involves their inability to sustain mortgage installment payments, resulting in the termination of sale and purchase agreements due to failure to settle mortgage obligations and associated liabilities. Employing a dual methodology of normative and socio-empirical juridical analysis, this study elucidates the tripartite legal relationships established within buyback guarantee agreements between developers, financial institutions, and purchasers. The findings identify critical legal issues, including the absence of specific statutory regulation, unequal bargaining power, unclear property valuation methods, inadequate notification procedures, and limited access to dispute resolution for purchasers. These deficiencies often lead to procedural unfairness and contravene the principle of good faith. The study concludes that the current framework, partially based on the Indonesian Civil Code, is insufficient for modern mortgage complexities. Therefore, it recommends regulatory intervention by the Financial Services Authority (OJK) to establish clear guidelines on obligations, valuation standards, and mandatory mediation or arbitration clauses. By harmonizing contractual freedom with consumer protection principles, these reforms aim to transform the buyback guarantee into a fairer and more transparent mechanism, ensuring equitable outcomes for all stakeholders in Indonesia's housing finance sector.